Analisis Pengaruh Pertumbuhan Ekonomi, Tingkat Pendidikan dan Kesehatan Terhadap Jumlah Penduduk Miskin di Bali Tahun 2011-2020 - Enia Helga Pratiwi; Nazaruddin Malik (Program Studi Ekonomi Pembangunan, 2022)
This study aims to determine the effect of economic growth, level of education and health on the number of poor people in the Regency/City of Bali Province. In this study, the high poverty rate in the Regency/City of the Province of Bali is a problem that will be studied. The method used in this study is a quantitative panel data method with the help of software eviews 9. The data used is secondary data, using panel data methods (cross-section) and (time series). The period in this analysis is 2007-2016 and 9 districts/cities in the province of Bali. The results showed that simultaneously the variable economic growth (X1) had a positive and significant effect on the number of poor people in the Regency/City of Bali Province. Meanwhile, the education level variable (X2) and the health variable (X3) have a negative and significant effect on the number of poor people in the Regency/City of Bali Province. This study aims to determine the effect of economic growth, level of education and health on the number of poor people in the Regency/City of Bali Province. In this study, the high poverty rate in the Regency/City of the Province of Bali is a problem that will be studied. The method used in this study is a quantitative panel data method with the help of software eviews 9. The data used is secondary data, using panel data methods (cross-section) and (time series). The period in this analysis is 2007-2016 and 9 districts/cities in the province of Bali. The results showed that simultaneously the variable economic growth (X1) had a positive and significant effect on the number of poor people in the Regency/City of Bali Province. Meanwhile, the education level variable (X2) and the health variable (X3) have a negative and significant effect on the number of poor people in the Regency/City of Bali Province.